Perancangan Aplikasi Pengelolaan Properti Berbasis Website - Cut Muthia Ramadhani; Noveri Lysbetti Marpaung; Sakti Hutabarat; Rahyul Amri; Edy Ervianto; Nurhalim; Suwitno (CSRID (Computer Science Research and Its Development Journal), 2026)
This study discusses the development of a web-based property management system designed to meet the needs of two types of users: administrators and tenants. The system was developed using the Research and Development (R&D) method with the Rational Unified Process (RUP) approach and implements the Model-View-Controller (MVC) architectural pattern. The application was built using the Laravel framework and MySQL database. It consists of two main interfaces: an administrator interface that includes a landing page, login page, and dashboard, and a tenant interface that is designed to be user-friendly. The features available in the administrator interface include property management, tenant data management, financial management, complaint handling, and user account management, all aimed at improving operational efficiency. System testing was conducted using SonarQube to evaluate code quality, PageSpeed Insights to assess application performance, and the User Experience Questionnaire (UEQ) to measure user experience. The test results indicate that the application meets various important quality aspects, including functional suitability, reliability, maintainability, performance efficiency, portability, compatibility, security, and usability. Despite the system’s many advantages, several areas for improvement remain. Suggested enhancements include integration with WhatsApp for better communication, a notification system to keep users updated, the addition of diverse payment options, and optimization of the user interface for a more responsive and attractive design. Therefore, the developed application is expected to improve the efficiency of property management and enhance user satisfaction, particularly for administrators managing property units, tenant data, finances, complaints, and user accounts.